Direct Synthesis of Nitrones via Transition-Metal-Free Ring-Opening of N-Tosylaziridines with the Nitrogen Atom of Various (E)-Aldoximes and (E)-Ketoximes - Li, Xing; Yan, Wenjing; Zhang, Rui; Chang, Honghong; Gao, Wenchao; Tian, Xiuping; Wei, Wenlong (Synthesis, 2019)
The KOH-, K2CO3-, or Et3N-catalyzed ring-opening reaction of N-tosylaziridines using the nitrogen atom of a series of (E)-aldoximes and (E)-ketoximes as a nucleophilic atom instead of an oxygen atom was developed to construct various nitrones under mild reaction conditions. Diverse (E)-aldoximes and (E)-ketoximes were demonstrated to be compatible with this reaction and the products of O-ring-opening reactions were not detected for most examples.
Keywords: nitrone; N-tosylaziridine; oxime; KOH; ring opening